Semidiurnal internal tide incoherence in the equatorial Pacific. Issue 7 (3rd July 2017) - Buijsman, Maarten C.; Arbic, Brian K.; Richman, James G.; Shriver, Jay F.; Wallcraft, Alan J.; Zamudio, Luis
Abstract: The jets in the equatorial Pacific Ocean of a realistically forced global circulation model with a horizontal resolution of 1 / 12.5 ° cause a strong loss of phase coherence in semidiurnal internal tides that propagate equatorward from the French Polynesian Islands and Hawaii. This loss of coherence is quantified with a baroclinic energy analysis, in which the semidiurnal‐band terms are separated into coherent, incoherent, and cross terms. For time scales longer than a year, the coherent energy flux approaches zero values at the equator, while the total flux is ∼500 W/m. The time variability of the incoherent energy flux is compared with the internal‐tide travel‐time variability, which is based on along‐beam integrated phase speeds computed with the Taylor‐Goldstein equation. The variability of monthly mean Taylor‐Goldstein phase speeds agrees well with the phase speed variability inferred from steric sea surface height phases extracted with a plane‐wave fit technique. On monthly time scales, the loss of phase coherence in the equatorward beams from the French Polynesian Islands is attributed to the time variability in the vertically sheared background flow associated with the jets and tropical instability waves. On an annual time scale, the effect of stratification variability is of equal or greater importance than the shear variability is to the loss of coherence. In the model simulations, low‐frequency equatorial jets do not noticeably enhance the dissipation of the internal tide, but merely decohere and scatter it. Key Points: The equatorial jets in the Pacific Ocean decohere equatorward propagating semidiurnal internal tides The time‐variable vertical shear flow and stratification cause incoherence on different time scales The equatorial jets do not cause increased internal tide dissipation in a 1/12.5° global ocean model